PENGEMBANGAN MEDIA ALAT PERAGA KOTAK BAPER (BELAJAR PERKALIAN) UNTUK MENINGKATKAN KEMAMPUAN PERKALIAN SISWA SD 2 GETASSRABI - Zakiyati, Nor Meilin; Lisanto, Hedi; Pratama, Meilisya Ulya Putri; Alvianna, Anggis; Hafis, Nanda Irmiyani; Setiawaty, Rani (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research is to: (1) develop learning media in the form of BAPER Box teaching aids; (2) find out the feasibility of BAPER Box teaching aids in the form of math addition material for fifth grade students. This research is an RD research that adopts development from Borg Gall. The subjects in this study were 15 students in class V SD 2 Getassrabi and the data collection instrument used was a questionnaire given to material experts, media experts, students and teachers of class V SD 2 Getassrabi to test the feasibility of learning media in the form of a questionnaire in the form of condition. The types of data generated are qualitative and quantitative data which are analyzed with the guideline of category assessment criteria to determine the feasibility of the product. The results of this study are; 1) the learning media that has been developed is in the form of a BAPER Box visual aid; 2) the feasibility of the media in the form of BAPER Box learning that has been developed is feasible with an average score of 3.1 based on the assessment of material experts at the final stage after improvement, design experts with an average acquisition score of 3.5 with a feasible assessment, the results of student responses with a proportion of 2.8 with adequate criteria, the results of class teacher responses with an average score of 3.4 with feasible criteria.